The Prediction of Internet Addiction in Female Students Based on Cloninger’s Temperament and Character - Neda Nejadhamdy (Journal of Modern Psychology, 2021)
The present study was conducted on female students of Allameh Tabataba'i University to predict Internet addiction through a seven-factor Cloninger model. The statistical population of the study consisted of all female students of Allameh Tabataba'i University studying in the academic year 2019-2020. Moreover, a sample population of 150 people was selected through the convenience sampling method. Young's Internet Addiction Test and Cloninger’s Temperament and Character Inventory (TCI-125) were administered to the sample population. The data were analyzed by Pearson’s correlation test, multiple regression. Results of Enter regression indicated that persistence dimension (b=-0.355) could account for 18.6% of variances of Internet addiction. The results of stepwise regression showed that persistence (b=-0.349) could predict 12.2% of variances of Internet addiction. Then, self-directedness was added to the prediction model which increased the explained variances of Internet addiction up to 15.4% of which 3.2% accounts particularly for self-directedness. This study may contribute to more accurate identification of involved factors in this phenomenon and provide a proper approach for prevention and treatment in line with those focused on evaluating the effective factors on Internet addiction.